A prospective cohort study of patients with peripheral T‐cell lymphoma in the United States. Issue 7 (2nd December 2016) - Carson, Kenneth R.; Horwitz, Steven M.; Pinter‐Brown, Lauren C.; Rosen, Steven T.; Pro, Barbara; Hsi, Eric D.; Federico, Massimo; Gisselbrecht, Christian; Schwartz, Marc; Bellm, Lisa A.; Acosta, Mark A.; Shustov, Andrei R.; et al.
Abstract : BACKGROUND: Long‐term survival in patients with aggressive peripheral T‐cell lymphoma (PTCL) is generally poor, and there currently is no clear consensus regarding the initial therapy used for these diseases. Herein, the authors analyzed treatment patterns and outcomes in a prospectively collected cohort of patients with a new diagnosis of nodal PTCL in the United States. METHODS: Comprehensive Oncology Measures for Peripheral T‐cell Lymphoma Treatment (COMPLETE) is a prospective multicenter cohort study designed to identify the most common prevailing treatment patterns used for patients newly diagnosed with PTCL in the United States. Patients with nodal PTCL and completed records regarding baseline characteristics and initial therapy were included in this analysis. All statistical tests were 2‐sided. RESULTS: Of a total of 499 patients enrolled, 256 (51.3%) had nodal PTCL and completed treatment records. As initial therapy, patients received doxorubicin‐containing regimens (41.8%), regimens containing doxorubicin plus etoposide (20.9%), other etoposide regimens (15.8%), other single‐agent or combination regimens (19.2%), and gemcitabine‐containing regimens (2.1%). Survival was found to be statistically significantly longer for patients who received doxorubicin (log‐rank P  = .03). After controlling for disease histology and International Prognostic Index, results demonstrated a trend toward significance in mortality reduction in patients who received doxorubicin compared with those who did not (hazard ratio, 0.71; 95% confidence interval, 0.48‐1.05 [ P  = .09]). CONCLUSIONS: To the authors' knowledge, there is no clear standard of care in the treatment of patients with PTCL in the United States. Although efforts to improve frontline treatments are necessary, anthracyclines remain an important component of initial therapy for curative intent. Cancer 2017;123:1174–1183. © 2016 American Cancer Society . Abstract : There is no clear standard of care in the treatment of patients with peripheral T‐cell lymphoma in the United States. Although efforts to improve frontline treatments are necessary, anthracyclines remain an important component of initial therapy for curative intent.